Interstitial lung disease in rheumatoid arthritis: A multidisciplinary problem in rheumatology and pulmonology - E. L. Nasonov; L. P. Ananyeva; S. N. Avdeev (Научно-практическая ревматология, 2018)
Rheumatoid arthritis (RA) is an immune-mediated rheumatic disease (IMRDs) characterized by chronic erosive arthritis and systemic damage to internal organs, leading to early disability and reduced life expectancy in patients. A particularly important place among the systemic manifestations of RA is occupied by interstitial lung diseases (ILD) – the most severe form of pulmonary pathology in RA, defined as RA-ILD, which is pathogenetically associated with risk factors (smoking, etc.) and autoimmune mechanisms underlying RA. RA-ILD is a subtype of RA characterized by a severe course and a poor prognosis и неблагоприятным прогнозом. The review presents new data regarding risk factors and biomarkers for RA-ILD; modern diagnostic capabilities based on the use of functional lung tests, high-resolution computed tomography, ultrasound examination of the lungs. Particular attention is paid to the efficacy and safety of pharmacotherapy, including methotrexate, biologics, JAK inhibitors, and antifibrotic therapy. An algorithm for the pharmacotherapy of RA-ILD has been proposed.